Investment in energy assets under uncertainty - Abadie, L.M .; Chamorro, J.M. (London : Springer, 2013)
This book aims to provide a rigorous yet pragmatic approach to the valuation and management of investments in the energy sector. Time and uncertainty pervade most if not all issues relevant to energy assets. They run from the early stage of prototype and demonstration to the ultimate abandonment and decommissioning. Risk in particular appears in several areas; thus, one can distinguish technical risk from financial.
Valuation made simple: No uncertainties, just time.- Theoretical foundations.- Analytical solutions.- Binomial lattices.- Finite difference methods.- Monte Carlo simulation.- Economic and technical background.- Valuation of energy assets: A single risk factor.- Valuation of energy assets: Two risk factors.- Valuation of energy assets: Three risk factors.- Value maximization and optimal management of energy assets.